2008
DOI: 10.1177/1352458507084650
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting incomplete recovery from relapses in multiple sclerosis: a prospective study

Abstract: Factors predicting incomplete recovery are more closely linked to the characteristics of the single relapse (extension and duration of tissue damage) than to the patient's genetic and environmental background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 32 publications
6
50
0
Order By: Relevance
“…Several studies identified attacks (i.e. relapses or the initial clinical events) with the impact on sphincteric [123][124][125][126][127] or pyramidal function [124,126,128] as being predictive of poorer long-term disability outcomes, while the cerebellar and brainstem attacks showed mixed results (for review, see [129] ). In contrast, attacks with the features of optic neuritis were associated with relatively more favourable disability outcomes [127,128,130] .…”
Section: Prognostic Value Of Relapsesmentioning
confidence: 99%
“…Several studies identified attacks (i.e. relapses or the initial clinical events) with the impact on sphincteric [123][124][125][126][127] or pyramidal function [124,126,128] as being predictive of poorer long-term disability outcomes, while the cerebellar and brainstem attacks showed mixed results (for review, see [129] ). In contrast, attacks with the features of optic neuritis were associated with relatively more favourable disability outcomes [127,128,130] .…”
Section: Prognostic Value Of Relapsesmentioning
confidence: 99%
“…Relapses presenting with pyramidal tract and sphincter disorders have a poor long-term prognosis when compared with relapses without involvement of these systems (39,40,41,42).…”
mentioning
confidence: 99%
“…57 Residual disability is seen in one third to half of all relapses [59][60][61][62] and is more likely if the relapse is severe, multifocal, initially slow to recover, and in people 30 years or older. 60 62 One study indicates that a lack of recovery from a relapse predicts incomplete remission of future relapses.…”
Section: Recovery From Individual Relapsementioning
confidence: 99%